Conceptual Strategy to Increase Crop Productivity under Sustainable Agriculture - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
Increasing global warming associated with constant emission of green house gases mainly CO2, illegal logging, expansion of agricultural land and indiscriminate human activities and increasing abiotic stresses have direct impact on climate change; thereby affecting crop productivity and aggravating hunger and life security. In this respect, about 2/3rd of arable land are affected with salinity and 1/3rd of it under semiarid conditions, thereby reducing crop productivity under these stress prone areas. To mitigate carbon pollution, several strategies are adopted such as sequestration of carbon dioxide from the atmosphere from the factory sites and injecting it deep in the soil profile using sophisticated technology in advanced countries, reforestation of plants, carbon fixation by plants. EPA in USA has recommended the plantation of trees in carbon polluted areas to reduce carbon pollution. We selected several native trees and shrubs in Northeast Mexico with carbon sequestration capacity ranging from 45 to 51% carbon namely; Eugenia caryophyllata 51.66%, Litsea glauscensens 51.34%, Rhus virens 50.35%, Forestiera angustifolia 49.47%, Gochantia hypoleuca 49.86%, Forestiera angustifolia 49.47%, Pinus arizonica 49.32%, Cinnamomum verum 49.34%. Bumelia celastrina 49.25%, Tecoma stans 48.79%, Acacia rigidula 48.23%, ….